Liquid-Liquid Equilibrium of Propionic Acid + H2O + 1-Pentanol and Propionic Acid + H2O + 1-Hexanol at Temperatures of 303.15 and 323.15 K - Amamehi, Ovelly Miryam; Rohma, Afishah Salsabila; Wiguno, Annas; Kuswandi, Kuswandi (Journal of Fundamentals and Applications of Chemical Engineering, 2024)
This study aims to measure the liquid-liquid equilibrium of the ternary system of propionic acid + H2O + 1-pentanol and propionic acid + H2O + 1-hexanol at temperatures of 303.15 and 323.15 K at atmospheric pressure. The primary equipment used in this study is an equilibrium cell with a heating jacket. The experiment lasted for 24 hours with time weighting, which included 4 hours of stirring using a magnetic stirrer. The remaining 20 hours were allotted for the solution to settle until perfect equilibrium occurred. Gas Chromatography with an FID-type detector was used to analyse the experimental results for composition. Other variables were tested by conducting experiments and the results were plotted on a ternary diagram with 8 tie lines for each system. The ternary diagram indicates that both systems adhere to the Treybal type I. The NRTL and UNIQUAC equations were used to correlate the research data from each system, resulting in a Root Mean Square Deviation (RMSD) of 3.20% of the equilibrium composition for each system.